2012
DOI: 10.5301/ru.2012.9206
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Oxidative Stress and Obesity in Prostate Disease

Abstract: Recent data suggest that chronic increment of reactive oxygen species (ROS) may be involved in the development and progression of chronic prostatic disease, such as BPH and PCa; adipose tissue produces bioactive substances called adipokines, also involved in the production of ROS. Our study aims to evaluate the relationship between obesity and oxidative stress in prostate disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Serenoa repens has been reported to have antioxidant activity (Habib, ); however, the effect we observed could be attributed primarily to its anti‐androgenic effects. It is known that androgen stimulation can increase oxidative stress in the prostate by activation of metabolic pathways, and anti‐androgens can reduce oxidative stress (Scavuzzo et al , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serenoa repens has been reported to have antioxidant activity (Habib, ); however, the effect we observed could be attributed primarily to its anti‐androgenic effects. It is known that androgen stimulation can increase oxidative stress in the prostate by activation of metabolic pathways, and anti‐androgens can reduce oxidative stress (Scavuzzo et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…IR directly promotes cell proliferation and contractility alterations of the prostate (Vikram et al , ), which has been identified as an independent predictor of LUTS and erectile dysfunction in patients (Russo et al , ). Both, IR and obesity, are related to the production of reactive oxygen species (ROS) and a state of low‐grade inflammation that in turn modifies the secretion of growth factors in prostatic tissue, increasing the size of the gland regardless of androgen stimulation (Ribeiro et al , ; Scavuzzo et al , ). During oxidative stress, there is increased production of nitric oxide (NO) by activation of inducible NO synthase.…”
Section: Introductionmentioning
confidence: 99%
“…In obesity there is development of insulin resistance, which leads to glucose intolerance and other alterations which can lead to the development of metabolic syndrome; this leads to altered reactive oxygen species (ROS) production and a low-grade inflammation status which subsequently alter the production of growth factors in prostatic tissue increasing the size of the gland in a non-androgen dependent mechanism [25,26]. Inflammation plays an important role, since ROS themselves can cause tissue damage, increasing nitric oxide production by activation of the inducible nitric oxide synthase (iNOS).…”
Section: Obesity and Bphmentioning
confidence: 99%